Corrigendum to "Comparison of additive and multiplicative feedforward control" [J. Process Control 111 (C) (2022) 1–7]. (May 2022) - Luyben, William L.
Abstract: The purpose of this note is to correct an error in a previous paper and to illustrate the effect the selection of the basic distillation control structure has on the performance of additive and multiplicative feedforward control structures.